Reflections on photographic aesthetics. Representation in photography - Muñoz Hincapié, Jaime (Estudios de Filosofía, 1995)
Since ancient times, reflection on the image of art has emerged as one of the tasks of philosophy, moreover, from art, philosophy has dealt with topics of great relevance to itself, such as imitation and knowledge, then imagination, the judgment, the truth, the interpretation. Photography emerged as a means of making images that questioned the fundamental principles of art, its relationship with nature, the traditional way of making images until then known; She also questioned the themes of representation or established genres, but art also questioned the incursion of the new medium into its domain.